IMPROVING THE STUDENTS'VOCABULARY MASTERY BY USING ENGLISH SONG AT MARKUS MIDDLE SCHOOL MEDAN - Lenna Sinaga; Sri Ninta Tarigan (English Language Teaching Prima Journal (ELT), 2023)
This research was aimed to find out the improving students’ vocabulary mastery by using english song . The subject of this research was third grade of Markus Middle School Medan. It was consisted of one class and 26 students as respondents. The object of this research was to improve students vocabulary mastery by using english song. Employing Classroom Action Research (CAR) with two cycles using quantitative methods to gather data through pre-tests and post-tests. The findings revealed that instructional media played a crucial role in enhancing students' listening skills, particularly addressing the limitations in their English vocabulary. This was substantiated by the mean score in the second cycle (60.76%), indicating a 20% improvement from the first cycle's mean score (40.76%). The conclusion drawn was that there was a significant improvement in the ability of class IX-C students at Markus Middle School to listen to a song, as evidenced by higher scores in both content and organization in the second cycle compared to the first. This success reflects a substantial achievement in enhancing students' listening skills.